THE EFFECT OF PROBLEM BASED LEARNING (PBL) STRATEGY, AND LEARNING MOTIVATION ON STUDENTS' CHEMISTRY LEARNING OUTCOMES - Mariyah Ulfah; Ahmad Noor Fatirul; Djoko Adi Walujo (Jurnal Mantik, 2022)
The purpose of this study was to determine the test results: (1) The Effect of Problem Based Learning (PBL) Strategies and Expository Methods on Students' Chemistry Learning Outcomes, (2) The Effect of High and Low Learning Motivation on Students' Chemistry Learning Outcomes, (3 ) Interaction Between Problem Based Learning (PBL) Strategy and Learning Motivation on Students' Chemistry Learning Outcomes. This experimental research was carried out using a 2x2 factorial design. The subjects in this study were students of class XI which consisted of four classes with 120 students. The subjects that became the focus of the experiment were classically randomized, namely four ABCD classes from SMAN 1 Sangkapura. The research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The results of the calculation show that: (1) Chemistry Learning Outcomes of students who are taught with Problem Based Learning (PBL) Strategy, namely Based on the table it turns out to be 0.000 <0.05, it can be said to be significant, (2) Chemistry Learning Outcomes of students who have high learning motivation and have Learning motivation is low, that is, based on the table, it turns out 0.013 <0.05, it can be said to be significant, and (3). Based on the table, 0.000 < 0.05, it can be said that there is an interaction between Problem Based Learning (PBL) Strategy, Expository Method, and Learning Motivation on Chemistry Learning Outcomes. Based on the results of the study, it was concluded that by using the Problem Based Learning (PBL) Strategy, the Expository Method, and Learning Motivation could improve students' Chemistry Learning Outcomes.